Potentiating effects of honey on antioxidant properties of lemon-flavoured black tea - Pereira, Carla (2013)
Health benefits including antioxidant potential of black tea (Camellia sinensis), lemon (Citrus limon) and honey bees (Apis mellifera) have been extensively reported. Nevertheless, nothing is reported about the effects of their concomitant use. Herein, those effects were evaluated in infusions of lemon-flavoured black tea with three different kinds of honey (light amber, amber and dark amber) from Lavandula stoechas, Erica sp. pl. and other indigenous floral species from north-east Portugal, a region with high amounts of this food product. Data obtained showed that the use of honey (dark amber > amber > light amber) potentiates the antioxidant activity of lemon-flavoured black tea, increasing the reducing power and lipid peroxidation inhibition properties, as also the antioxidant contents such as phenolics, flavonoids and organic acids including ascorbic acid.